Integrity violations in Malaysian government departments: the organisational fraud triangle perspective / Afzal Izzaz Zahari - Zahari, Afzal Izzaz (2020)
The Association of Certified Fraud Examiners (ACFE) in 2019 estimates that the world loses USD6.3 billion dollars due to integrity violations, such as fraud and corruption. Governments are the highest spending organisations with an average of 41.9% of Gross Domestic Capita (GDP), as such governments are highly vulnerable to experience the ill effects of integrity violation. Integrity violation causes economic loss and has a negative impact on the organisation through an increase in costs of service delivery, the loss of income, reduced productivity and efficiency. Past studies on integrity violation tend to concentrate on the private sector in developed countries. Currently, limited studies focused on the integrity violation in the public sector, especially in the context of developing countries that warrant more studies to be conducted. According to Organisational Fraud Triangle Theory (OFTT), three main factors are contributing to integrity violation; leadership, ethical culture, and control systems. Leaders are responsible for shaping the tone from the top of the organisation. Strong organisational ethical cultures promote a positive work environment amongst the employees. Ethical culture infuses higher levels of understanding and improved reason towards the repercussions of conducting integrity violations. Internal control is a control mechanism that monitors and mitigates potential integrity violation from taking place in the organisation. Currently, limited empirical studies examined the three factors contributing to integrity violation, as proposed by OFTT. This study aims to examine whether these three factors affect the levels of integrity violation. Past studies did not examine all the three factors simultaneously in a single study to identify which of the elements has significant impacts on integrity violation. This study subsequently investigated whether integrity climate has any direct effect on integrity violations and if it mediates the relationship between organisational fraud triangle components and integrity violations. There were 382 returned questionnaire surveys (68.34%) out of the 559 questionnaire surveys distributed to Malaysian government departments. The findings show that ethical leadership and integrity climate have a significant relationship with integrity violations. However, internal control systems were not a significant factor in integrity violations in the Malaysian government department. These findings indicate that ethical leadership, ethical culture, and integrity climate are important components that can be used to mitigate integrity violations. The organisational strategy to improve the overall integrity could be focused on aspects of leadership quality, improving ethical culture, and infusing positive working environment through integrity climate. The overalls results suggest that effective organisational management should focus on the development of ethical leadership structures, promoting ethical culture values and a healthy integrity climate in order to control or mitigate the levels of integrity violation.